Pengaruh Dukungan Organisasi Dan Kompensasi Terhadap Kinerja Awak Kapal Tunda Melalui Kepuasan Kerja Pada PT. Aman Bahari Kuala Tanjung - Dicky Arie Ananta Siregar; Fajar Pasaribu (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
The purpose of this study was to examine and analyze the effect of organizational support and compensation on performance through job satisfaction of tugboat crews at PT. Aman Bahari Kuala Tanjung directly or indirectly. The approach used in this research is a causal approach. The population in this study were all tugboat crews at PT. Aman Bahari Kuala Tanjung. The sample in this study using a saturated sample of 57 tugboat crew at PT. Aman Bahari Kuala Tanjung. Data collection techniques in this study used documentation, observation, and questionnaires. The data analysis technique in this study uses a quantitative approach using statistical analysis using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study uses the PLS (Partial Least Square) software program. The results of this study prove that directly organizational support, compensation and job satisfaction have a significant effect on performance and indirectly organizational support and compensation have a significant effect on performance through crew job satisfaction. tugs at PT. Aman Bahari Kuala Tanjung